Spatio-temporal dynamics of land use and their socioecological relationship in ejido Barrón, Mazatlán, Sinaloa - Alvarez Tostado Ríos, Paloma; Silva Gómez, Sonia Emilia; Pérez Osorio, Gabriela; Castelán Vega, Rosalía del Carmen; Rivera Rodríguez, Laura Beatriz (Acta Universitaria, 2026)
Land use change has an impact on ecosystem dynamics, affecting both ecosystem services and social-ecological interactions. In the case of ejido Barrón, these changes can be associated with the growth of the settlement and agricultural activities. Thus, an identification and analysis of land cover changes and their relationship with social-ecological dynamics in the period from 2005 to 2023 was carried out. Satellite images were processed with geographic information systems (GIS), and a statistical analysis was performed using transition matrices and Markov chains. A decrease in the area occupied by low deciduous forest and riparian vegetation as well as an increase in the settlement and parceled area were observed. This dynamic alters the ecosystemic and socioeconomic balance, showing the need to implement sustainable strategies such as biofertilizers usage and rural tourism that allow better management of biotic and abiotic factors.